2022
DOI: 10.1002/cam4.4667
|View full text |Cite
|
Sign up to set email alerts
|

Different patients, different preferences: A multicenter assessment of patients' personality traits and anxiety in shared decision making

Abstract: Objective Patient‐centered care and shared decision making (SDM) are generally recognized as the gold standard for medical consultations, especially for preference‐sensitive decisions. However, little is known about psychological patient characteristics that influence patient‐reported preferences. We set out to explore the role of personality and anxiety for a preference‐sensitive decision in bladder cancer patients (choice of urinary diversion, UD) and to determine if anxiety predicts patients' participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Design. Prospective, multicenter observational study from Germany described the role of personality and anxiety in patient preference in the context of choosing UD [ 16 ]. Patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Design. Prospective, multicenter observational study from Germany described the role of personality and anxiety in patient preference in the context of choosing UD [ 16 ]. Patients.…”
Section: Resultsmentioning
confidence: 99%
“…In the second group, we found four studies focusing on shared decision-making and a more personalized approach to the patient while choosing UD, involving studies describing personality [ 16 ], patients’ values and goals [ 17 , 18 ], and role of patient–physician dialogue in the context of choosing UD [ 19 ]. The main drawbacks of all four studies are small sample sizes, but most of all, the correlations between all assessed features and their impact on choice of UD were not evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In order to establish the context specificity of the API-Uro, and highlight the relevance of assessing patients’ preference for active participation in the specific decision contexts, we compared the participation preference for treatment decisions vs. diagnostic decisions in both studies. Patients were categorized based on a taxonomy from the literature [ 30 , 50 , 62 ] into either delegators (participation preference ≤ 40) or participators (participation preference > 40). Table 5 illustrates the differences in participation preference depending on the decision context and the respective diagnoses of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…A study nurse approached patients, and after giving informed consent, they completed a set of self-report measures, including the German API [ 45 ], the original case vignettes API-OV [ 23 ], and the urooncological case vignettes API-Uro [ 46 ]. More details on the study procedure and additional measured constructs can be found in Köther et al [ 50 ]. The study was approved by the ethics committee of the Medical Faculty of Mannheim of the University of Heidelberg (MA-2019-727N).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation